Hemorrhagic Cerebrovascular Pathology in the Pediatric Population - Guerrero, Waldo R.; Dandapat, Sudeepta; Ortega-Gutierrez, Santiago (Frontiers in Neurology, 2020)
Hemorrhagic cerebrovascular disease in the pediatric population can have devastating and long-term effects. Progress in the fields of genetics, neuroimaging, pharmacology, and surgical techniques has led to improved diagnosis and management of pediatric cerebrovascular diseases. In this review we discuss the current etiologies and medical and surgical treatments of hemorrhagic cerebrovascular pathology affecting infants and children. A special emphasis is placed on neuroendovascular treatment options. Increased knowledge about this unique pathology and the medical and therapeutic options will empower practitioners to more quickly and accurately identify and accurately treat hemorrhagic diseases in the pediatric population.